High-Temperature Rheological and Molecular Dynamics Analysis of Asphalt Modified with SiC Filler - Song, Meijun (Langmuir : the ACS journal of surfaces and colloids, 2025)
This study aims to address the increasingly complex environmental demands by enhancing the high-temperature durability of asphalt pavements during service, study on the effect and mechanism of silicon carbide (SiC) ceramic micropowder on the performance of modified asphalt. The rheological properties and modification mechanism of SiC-modified asphalt were analyzed using Saturates, Aromatics, Resins, and Asphaltenes (SARA) fraction analysis, viscosity tests, dynamic shear rheological (DSR) tests, Fourier transform infrared spectroscopy (FTIR), and molecular dynamics (MD) simulations. The results show that SiC ceramic micropowder, with its high specific surface area and rich porous structure, effectively adsorbs the lighter components of asphalt, significantly improving its viscosity and high-temperature stability. Rheological tests demonstrate that SiC ceramic micropowder significantly increases the viscosity and rutting factor of asphalt, with a 34.74% improvement in G*/sin δ at 60 °C, indicating a marked enhancement in high-temperature performance. FTIR spectra confirm that the modification of asphalt by SiC is a physical process, as no new functional groups were formed. MD simulations reveal that the interfacial energy between SiC and asphalt is negative, indicating an attractive interaction between the two phases. The selective adsorption of SiC on the SARA fractions follows the order: aromatics > resins > saturates > asphaltenes, which promotes the aggregation of saturates and aromatics on the SiC surface, altering the composition of asphalt. In conclusion, the interfacial interactions and selective adsorption characteristics of SiC ceramic micropowder significantly enhance the viscosity and high-temperature performance of asphalt. This study provides a theoretical foundation for the practical application of SiC ceramic micropowder in high-temperature asphalt environments and offers valuable insights for its engineering applications